Heat stress in rice vermicelli manufacturing factories. (2nd October 2018) - Seng, Melvin; Ye, Meishan; Choy, Kenneth; Ho, Sweet Far
ABSTRACT: Objective : This study provides an assessment of heat stress in indoor rice vermicelli manufacturing factories. Methods : Worker interviews and heat stress assessments were conducted in food manufacturing factories in Singapore. The Wet Bulb Globe Temperature (WBGT) and Heat Stress Index (HSI) were used as heat stress indicators. Results : The highest WBGT and HSI levels recorded in the rice vermicelli manufacturing factories were 36.68°C and 3777 in the drying and steaming process respectively. These levels were above the recommended permissible HSI and WBGT action limit for heat exposure and considered to be high risk. Conclusion : Workers in indoor rice vermicelli manufacturing factories can be exposed to heat stress, and the current measures in place may not be sufficient to protect workers against heat stress injuries. Preventive measures such as engineering controls and heat acclimatization programs are important.